Economic freedom and antisemitism. Issue 2 (27th April 2021) - Berggren, Niclas; Nilsson, Therese
Abstract: We examine how variation in antisemitism across countries can be explained by economic freedom. We propose two mechanisms. First, the more economic freedom, the greater the scope of market activities. If people perceive Jews as particularly skilful at doing business at the expense of others, a greater reliance on markets can increase antisemitism. Second, a key type of institution undergirding the market is an effective and fair legal system, or the rule of law. The stronger the rule of law, the smaller the risk for exploitative behaviour, and the less hostile people will be towards groups seen as exploiters. If Jews are seen as such, more economic freedom reduces antisemitism. We use the ADL Global 100 survey of antisemitic attitudes and relate them, for up to 106 countries, to the Economic Freedom of the World index and its five areas. Our empirical findings confirm the two predictions: The more economic openness, the more antisemitism; and the stronger the rule of law, the less antisemitism. These findings indicate a complex relationship between markets and attitudes towards Jews.